Correlation between polar surface area and bioferroelectricity in DNA and RNA nucleobases - Yam, See Chuan; Zain, Sharifuddin Md; Lee, Vannajan Sanghiran; Chew, Khian Hooi (Springer Verlag, 2018)
Abstract.: We have performed computational molecular modelling to study the polarization switching and hysteresis loop behaviours of DNA and RNA nucleobases using the PM3 semi-empirical quantum mechanical approaches. All the nucleobases: adenine (A), thymine (T), guanine (G), cytosine (C), and uracil (U) were modelled. Our study indicates that all the nucleobases exhibit a zero-field polarization due to the presence of polar atoms or molecules such as amidogen and carbonyl. The shape of polarization Pversus an applied electric field E hysteresis loop is square, implying typical ferroelectrics behaviour. The total energy U as a function of an applied electric field E exhibits a butterfly-like loop. The presence of zero-field polarization and ferroelectrics hysteresis loop behaviours in nucleobases may support the hypothesis of the existence of bioferroelectricity in DNA and RNA. We also found an interesting relationship between the minimum electric field required for switching EC and the ratio of the topological polar surface area (TPSA) to the total surface area (TSA) of a nucleobase. In particular, the EC of a nucleobase is inversely proportional to the TPSA/TSA ratio. This work may provide useful information for understanding the possible existence of ferroelectricity in biomaterials.